SINTESIS SERBUK BARIUM HEKSAFERIT YANG DITAMBAH DENGAN LOGAM Mn SEBAGAI MATERIAL ANTI RADAR - Khalilurrahman -; Susilawati -; Kosim - (Jurnal Penelitian Pendidikan IPA, 2016)
Barium Heksaferit (BaFe12-xMnxO19) powder synthesis was added with Mn metal using coprecipitation method. The purpose of adding these metals to see the effect of adding Mn metal and calcination temperature of the powder color change Barium Heksaferit. The value of x in the addition of Mn metal in Barium Heksaferit is x = 0 ; 0.2 ; 0.4 ; 0.6 and calcined for 4 hours at a temperature of 400 , 600 and 800 oC. The addition of Mn metal and calcination temperature rise resulting color more brown powderKeyword: Sintesis, Barium M-heksaferit‚ Mangan (Mn)‚ kopresipitasi